Paediatric rhinitis: position paper of the European Academy of Allergy and Clinical Immunology. Issue 9 (19th August 2013) - Roberts, G.; Xatzipsalti, M.; Borrego, L. M.; Custovic, A.; Halken, S.; Hellings, P. W.; Papadopoulos, N. G.; Rotiroti, G.; Scadding, G.; Timmermans, F.; Valovirta, E.
Abstract: Rhinitis is a common problem in childhood and adolescence and impacts negatively on physical, social and psychological well‐being. This position paper, prepared by the European Academy of Allergy and Clinical Immunology Taskforce on Rhinitis in Children, aims to provide evidence‐based recommendations for the diagnosis and therapy of paediatric rhinitis. Rhinitis is characterized by at least two nasal symptoms: rhinorrhoea, blockage, sneezing or itching. It is classified as allergic rhinitis, infectious rhinitis and nonallergic, noninfectious rhinitis. Similar symptoms may occur with other conditions such as adenoidal hypertrophy, septal deviation and nasal polyps. Examination by anterior rhinoscopy and allergy tests may help to substantiate a diagnosis of allergic rhinitis. Avoidance of relevant allergens may be helpful for allergic rhinitis (AR). Oral and intranasal antihistamines and nasal corticosteroids are both appropriate for first‐line AR treatment although the latter are more effective. Once‐daily forms of corticosteroids are preferred given their improved safety profile. Potentially useful add‐on therapies for AR include oral leukotriene receptor antagonists, short bursts of a nasal decongestant, saline douches and nasal anticholinergics. Allergen‐specific immunotherapy is helpful in IgE‐mediated AR and may prevent the progression of allergic disease. There are still a number of areas that need to be clarified in the management of rhinitis in children and adolescents.